5-HT1F Receptor Agonist Ameliorates Mechanical Allodynia in Neuropathic Pain via Induction of Mitochondrial Biogenesis and Suppression of Neuroinflammation - Zhang, Long-Qing; Zhou, Ya-Qun; Li, Jia-Yan; Sun, Jia; Zhang, Shuang; Wu, Jia-Yi; Gao, Shao-Jie; Tian, Xue-Bi; Mei, Wei (Frontiers in Pharmacology, 2022)
Neuropathic pain is a devastating disease that affects millions of people worldwide. Serotonin (5-hydroxytryptamine, 5-HT) is involved in pain modulation. Several lines of evidence have indicated that 5-HT1F receptor agonists are potent inducers of mitochondrial biogenesis. In this study, we tested the hypothesis that 5-HT1F receptor agonists ameliorate mechanical allodynia in neuropathic pain via the induction of mitochondrial biogenesis and suppression of neuroinflammation. Male Sprague–Dawley rats were used to establish a neuropathic pain model via spared nerve injury (SNI). The paw withdrawal threshold (PWT) was used to evaluate mechanical allodynia. Real-time polymerase chain reaction was used to examine the mitochondrial DNA (mtDNA) copy number. Western blotting and immunofluorescence were used to examine the expression of target proteins. Our results showed that mitochondrial biogenesis was impaired in the spinal cord of rats with SNI. Moreover, activation of PGC-1α, the master regulator of mitochondrial biogenesis, attenuates established mechanical allodynia in rats with neuropathic pain. In addition, the neuronal 5-HT1F receptor is significantly downregulated in the spinal cord of rats with neuropathic pain. Furthermore, the selective 5-HT1F receptor agonist lasmiditan attenuated established mechanical allodynia in rats with neuropathic pain. Finally, lasmiditan (Las) treatment restored mitochondrial biogenesis and suppressed neuroinflammation in the spinal cord of rats with SNI. These results provide the first evidence that lasmiditan ameliorates mechanical allodynia in neuropathic pain by inducing mitochondrial biogenesis and suppressing neuroinflammation in the spinal cord. Inducers of mitochondrial biogenesis may be an encouraging therapeutic option for the management of neuropathic pain.